Integrating supportive care into the multidisciplinary management of lung cancer: we can't wait any longer. Issue 7 (3rd July 2022) - Avancini, Alice; Belluomini, Lorenzo; Borsati, Anita; Riva, Silvia Teresa; Trestini, Ilaria; Tregnago, Daniela; Dodi, Alessandra; Lanza, Massimo; Pompili, Cecilia; Mazzarotto, Renzo; Micheletto, Claudio; Motton, Massimiliano; et al.
ABSTRACT: Introduction: Due to important achievements in terms of diagnostic and therapeutic tools and the complexity of the disease itself, lung cancer management needs a multidisciplinary approach. To date, the classical multidisciplinary team involves different healthcare providers mainly dedicated to lung cancer diagnosis and treatments. Nevertheless, the underlying disease and related treatments significantly impact on patient function and psychological well-being. In this sense, supportive care may offer the best approach to relieve and manage patient symptoms and treatment-related adverse events. Areas covered: Evidence reports that exercise, nutrition, smoking cessation, and psychological well-being bring many benefits in patients with lung cancer, from both a physical and socio-psychological points of view, and potentially improving their survival. Nevertheless, supportive care is rarely offered to patients, and even less frequently these needs are discussed within the multidisciplinary meeting. Expert opinion: Integrating supportive care as part of the standard multidisciplinary approach for lung cancer involves a series of challenges, the first one represented by the daily necessity of specialists, such as kinesiologists, dietitians, psycho-oncologists, able to deliver a personalized approach. In the era of precision medicine, this is an essential step forward to guarantee comprehensive and patient-centered care for all patients with lung cancer.